2014
DOI: 10.1007/s13258-014-0260-3
|View full text |Cite
|
Sign up to set email alerts
|

An automated analysis pipeline for a large set of ChIP-seq data: AutoChIP

Abstract: Although there are many applications available for the analysis of chromatin immunoprecipitation with massively parallel DNA sequencing (ChIP-seq), users need some knowledge about the installation, alignment, and peak calling procedures prior to the analysis. Here, we present an easy-to-use application for ChIP-seq analysis called AutoChIP. With AutoChIP, installation of necessary programs, alignment of unmapped reads to a reference genome, and identification of genome-wide binding sites can be done in a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The cancer tissue showed higher levels of arginine, betaine, glutamate, lysine, and taurine and lower levels of glutamine, hypoxanthine, isoleucine, lactate, methionine, pyruvate, and tyrosine relative to normal tissue. In another example, Dr. Kim carried out HR-MAS NMR experiments to distinguish metabolic changes in human hepatocellular carcinomas (HCCs) and colorectal liver metastases (CRLMs) and then confirmed that each tissue sample was clearly classified into different groups by multivariate analysis (Kim et al 2014a). Good separation among tumors and non-tumorous hepatic parenchyma was observed in OPLS-DA loading plots.…”
mentioning
confidence: 90%
“…The cancer tissue showed higher levels of arginine, betaine, glutamate, lysine, and taurine and lower levels of glutamine, hypoxanthine, isoleucine, lactate, methionine, pyruvate, and tyrosine relative to normal tissue. In another example, Dr. Kim carried out HR-MAS NMR experiments to distinguish metabolic changes in human hepatocellular carcinomas (HCCs) and colorectal liver metastases (CRLMs) and then confirmed that each tissue sample was clearly classified into different groups by multivariate analysis (Kim et al 2014a). Good separation among tumors and non-tumorous hepatic parenchyma was observed in OPLS-DA loading plots.…”
mentioning
confidence: 90%